Implementasi Model Pembelajaran Mind Map Sebagai Media Pembelajaran Untuk Meningkatkan Kemampuan dan Aktivitas Belajar IPA Siswa - Komang Teguh Hendra Putra (Purwadita : Jurnal Agama dan Budaya, 2021)
The purpose of this study is to increase students' activities and learning abilities through a mind map learning model for grade VI students of SD Negeri 9 Sumerta for the 2018/2019 academic year. The subjects in the study were 30 students of class VI. Data analysis of student learning outcomes after the first cycle of action can be seen that the average value is 53.57 with classical learning completeness reaching 25%. After the second cycle of action the average score was 72.31 with classical learning completeness 76.92%, while the average value in the third cycle was 89.64 with classical learning completeness reaching 96.43%. The results of the analysis of student activities in the first cycle of action obtained results of 60% with sufficient criteria. Student activity in the second cycle reached 73.33% with good criteria, while in the third cycle it reached 87% with very good criteria. Based on the results of this study, it is recommended that teachers use the Mind Map learning model as a medium in learning in order to improve students understanding and improve student learning abilities. Keywords: Mind Map, Media, Science, Learning Ability